2005
DOI: 10.1080/11250000509356647
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric pattern and biometry of adult Trichoptera (Italian species)

Abstract: Morphometric characters of 961 adult caddisflies, belonging to 327 taxa of the Italian Trichopteran fauna were observed and measured. Sexual dimorphism is reflected in the smaller mean size of males, with mean differences in body length of 12.57%. For the order Trichoptera, regressions of the relationships among body dimensions have been used to estimate the value of exponent b and coefficient a of the allometric function y = a * x b , a power function that describes these relationships very well. The lengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Kovats (1990) reported a very strong linear relationship between forewing length and forewing area (R² ! These relationships confirmed our hypothesis that flight morphological parameters are strongly correlated with one another and justified the common use of forewing length for the determination of the size of a species in the order Trichoptera (Malicky, 2004;Goretti et al, 2005). Using a much higher number of replications (N = 15), we tested individuals of 26 different species belonging to 13 genera of Limnephili-dae and compared the arithmetic means of the measured flight parameters.…”
Section: Correlation Between Morphological Parameterssupporting
confidence: 81%
See 4 more Smart Citations
“…Kovats (1990) reported a very strong linear relationship between forewing length and forewing area (R² ! These relationships confirmed our hypothesis that flight morphological parameters are strongly correlated with one another and justified the common use of forewing length for the determination of the size of a species in the order Trichoptera (Malicky, 2004;Goretti et al, 2005). Using a much higher number of replications (N = 15), we tested individuals of 26 different species belonging to 13 genera of Limnephili-dae and compared the arithmetic means of the measured flight parameters.…”
Section: Correlation Between Morphological Parameterssupporting
confidence: 81%
“…Because we used preserved material for this study, the primary focus was on morphological parameters and indices, such as forewing length, wing area, relative wing length, male-to-female wing ratio and aspect ratios. 0.97) for five North American Hydropsychidae species, and Goretti et al (2005) found a very strong linear relationship between forewing length and body length (R² = 0.96; ln-transformed) for 961 individuals belonging to 327 Italian caddisfly taxa. 0.97) for five North American Hydropsychidae species, and Goretti et al (2005) found a very strong linear relationship between forewing length and body length (R² = 0.96; ln-transformed) for 961 individuals belonging to 327 Italian caddisfly taxa.…”
Section: Correlation Between Morphological Parametersmentioning
confidence: 91%
See 3 more Smart Citations